8. VALUE OF RAJAN'S HEART FAILURE (R-HF) SCORE IN PREDICTING SHORT-TERM OUTCOMES IN PATIENTS WITH ACUTE DECOMPENSATED HEART FAILURE (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the value of Rajan’s Heart Failure (R-hf) score in predicting 3-month cardiovascular outcomes (CVOs) in patients with acute decompensated heart failure (ADHF).Methods: A combined prospective and retrospective cohort study was conducted on 233 patients (median age: 67 years; 52.9% female) hospitalized for ADHF. The R-hf score was calculated by multiplying the estimated glomerular filtration rate (eGFR, mL/min/1.73m²), left ventricular ejection fraction (LVEF, %), and hemoglobin level (g/dL), then dividing by NT-proBNP levels (pg/mL). Risk categories were stratified as very low (≥50), low (≥10 to
Keywords: acute decompensated heart failure; cardiovascular events; prognosis; R-hf risk score; short-term outcomes.